45.5k views
5 votes
Evaluate each function. Step by step.

1) k(t) = -2|3t| + 2; Find k(-5)

2) g(n)=-3n^2+3+2n; Find g(-3)​

User Heroin
by
4.9k points

1 Answer

0 votes

Answer:

Substitute what t and n equals to in the equation and just solve using algebra.

So number 2, plug in -3 where ever the variable N is located in and solve.

g(-3) = 3(-3)^2+3+2(-3) ---> g(-3) = 27+3-6 ---> g(-3) = 24 That's the answer for 2.

For 1

plug in -5 into the t variable and solve.

k(t) = -2 |3(-5)| + 2 Since the || is between the 3 and 5, answer will be positive.

k(t) = -2(15)+2

k(t) = -28

Explanation:

User Cogle
by
5.6k points